Teenagers' Social Construction of "Good" and "Bad" Women': A Study of Karin Novilda's Vlogs Through Berger and Luckmann's Theory - Nurul Hidayati, Mega; Agus Riani, Yuyun (Social Sciences and Humanities Reviews, 2025)
Background: The categorization of women as “good” or “bad” remains deeply embedded in patriarchal values, often perpetuated through family, religion, and social environments. With the rise of digital media, especially platforms like YouTube, adolescents are exposed to alternative representations of womanhood, such as those exemplified by public figure Karin Novilda (Awkarin). These portrayals challenge conventional gender norms and prompt young audiences to reinterpret established social values. Aims: This study explores how teenagers socially construct the concepts of “good” and “bad” women and how these constructions are reflected in their perceptions of Karin Novilda’s online persona. It also seeks to examine the persistence of gender-based double standards in adolescents’ judgments of public figures. Methods: Using a qualitative approach and the constructivist framework of Berger and Luckmann, the study engaged 12 adolescents aged 16–19 through in-depth interviews. Thematic analysis was employed to understand how social values are externalized, objectified, and internalized through social interactions and media exposure. Result: Findings reveal that teenagers associate the notion of a “good woman” with obedience, modesty, and conformity to religious and familial values. In contrast, expressive behavior, particularly on social media, is often deemed inappropriate. Despite this, many respondents still consume content from figures like Karin, showing a dissonance between moral judgment and digital engagement. Gender-based double standards were also evident, with women receiving harsher criticism than men for similar behaviors. Conclusion: This study concludes that teenagers’ perceptions are shaped by a dynamic social construction process influenced by traditional norms and digital media. While dominant values still persist, signs of critical reflection and negotiation are emerging among adolescents. These findings underscore the need for integrating critical media literacy and gender education into youth development strategies to foster more equitable perspectives on gender roles.